1970
DOI: 10.4143/crt.2013.212
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Prognostic Factors for Distant Metastasis after Induction Chemotherapy Followed by Concurrent Chemoradiotherapy for Head and Neck Cancer

Abstract: Purpose The aim of this study is to identify the prognostic factors of distant metastasis (DM) after induction chemotherapy (IC) followed by concurrent chemoradiotherapy (CRT) for locoregionally advanced head and neck cancer (HNC). Materials and Methods A total of 321 patients with HNC who underwent IC followed by CRT treated between January 2005 and December 2010 were analyzed retrospectively. IC consisted of three courses of docetaxel (70 mg/m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…We find an overlapping clinical parameter, namely node-stage, between these two clinical models. Indeed high node stage is hypothesized to be one of the major risk factors for the development of distant metastasis [21,22]. We also see some discrepancies between the two clinical models.…”
Section: Plos Onementioning
confidence: 75%
“…We find an overlapping clinical parameter, namely node-stage, between these two clinical models. Indeed high node stage is hypothesized to be one of the major risk factors for the development of distant metastasis [21,22]. We also see some discrepancies between the two clinical models.…”
Section: Plos Onementioning
confidence: 75%
“…Furthermore, the location of lymph node involvement may suggest which patients stand to gain a longer distant metastasis-free survival, as shown in a retrospective study by Kim et al, who determined that patients with present versus absent lower neck nodal involvement had a significantly lower 5-year distant metastasis-free survival rate (34.3% versus 55.2%, P = 0.008) [ 40 ]. Additionally, the same study determined that patients with hypopharyngeal SCC may be at higher risk of DF than those with laryngeal tumors (the risk for patients with oropharyngeal and oral cavity disease being somewhere in the middle) [ 40 ]. A meta-analysis by Zhang et al [ 41 ] indicated that the ICT approach significantly reduced the DFR in patients with unresectable disease.…”
Section: The Role Of Ict In Patients With High-risk Scchnmentioning
confidence: 99%
“…However, the results showed that the locations of LN invasion had no statistical relationship with either DM or OS rate. In a study of head neck cancer, lower-neck node involvement and poor response to induction chemotherapy were strongly associated with DM-free survival (Kim et al, 2015). ACC cells in LN may extend to the membrane structure with a result of adjacent soft tissue involvement.…”
Section: Discussionmentioning
confidence: 98%